Amber Light Control of Peptide Secondary Structure by a Perfluoroaromatic Azobenzene Photoswitch. (26th January 2023) - Cataldi, Eleonora; Raschig, Martina; Gutmann, Marcus; Geppert, Patrick T.; Ruopp, Matthias; Schock, Marvin; Gerwe, Hubert; Bertermann, Rüdiger; Meinel, Lorenz; Finze, Maik; Nowak‐Król, Agnieszka; Decker, Michael; et al.
Abstract: The incorporation of photoswitches into the molecular structure of peptides and proteins enables their dynamic photocontrol in complex biological systems. Here, a perfluorinated azobenzene derivative triggered by amber light was site‐specifically conjugated to cysteines in a helical peptide by perfluoroarylation chemistry. In response to the photoisomerization ( trans → cis ) of the conjugated azobenzene with amber light, the secondary structure of the peptide was modulated from a disorganized into an amphiphilic helical structure. Abstract : When amber means "go" : A perfluorinated azobenzene was synthesized and stapled to free cysteines within a helical peptide by using site‐selective perfluoroarylation chemistry. Illumination experiments proved successful change of the peptide's secondary structure in response to amber light.